Indicador de salubridade ambiental relacionada ao consumo de energia e água em municípios lindeiros e não lindeiros ao lago de Itaipu da bacia hidrográfica do Paraná - Cabral, Ana Claudia (2014)
Environmental sanitation includes some actions to society and the environment, among some of these actions may be cited the potable water supply, sanitary waste disposal, urban drainage and even the control of diseases arising vectors (insects or animals that are used as vehicles by diseases for infection) in a population. Given the great importance of environmental sanitation, new tools were created to assist in data collect and perform the related activities, finally, as one of these tools, there is the environmental health indicator (EHI). The EHI is calculated using some data related to environmental sanitation practices, these factors should be analyzed separately, for this it is necessary to conduct investigations into each of the factors, for the implementation of the EHI, each of the activities within the environmental sanitation is called first-order indicators, to facilitate the surveys are divided into second-order indicators. The data used for the calculation of the EHI were acquired through surveys and research in databases, and the results obtained from these calculations represent the environmental health of each of the studied areas. One of the uses proposed for these results is the possibility of using it to guide management plans for studied areas, which may improve the quality of life of the local population. Simultaneously to the EHI calculation, this study raised the average consumption of electricity and water in the municipalities belonging to the studied area, and performed an analysis to see if there is a relation between the amount spent and one of the sub-indicators present in the EHI, with regard to social and economic characteristics of the studied population. By comparing the studied areas, the paper also proposes to check the influence of royalties (monetary value paid by Itaipu, as a form of mitigation through flooded areas to the cities surrounding the lake of Itaipu) on the environmental health of the municipalities belonging to Paraná III watershed.